Особливості нейрональної активності фронтальної кори щурів при пентиленететразоловому кіндлінзі = The peculiarities of rats frontal cortex neuronal activity during pentylenetetrazol kindling - Denisenko, O. B.; Shandra, Al. Al.; Vastyanov, R. S. (Journal of Education, Health and Sport, 2015)
Denisenko О В, Shandra Al Al, Vastyanov R S. Особливості нейрональної активності фронтальної кори щурів при пентиленететразоловому кіндлінзі = The peculiarities of rats frontal cortex neuronal activity during pentylenetetrazol kindling. Journal of Education, Health and Sport. 2015;5(5):342-354. ISSN 2391-8306. DOI 10.5281/zenodo.17879 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A342-354 https://pbn.nauka.gov.pl/works/561485 http://dx.doi.org/10.5281/zenodo.17879 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 20.05.2015. УДК 612.825.1 ОСОБЛИВОСТІ НЕЙРОНАЛЬНОЇ АКТИВНОСТІ ФРОНТАЛЬНОЇ КОРИ ЩУРІВ ПРИ ПЕНТИЛЕНЕТЕТРАЗОЛОВОМУ КІНДЛІНЗІ THE PECULIARITIES OF RATS FRONTAL CORTEX NEURONAL ACTIVITY DURING PENTYLENETETRAZOL KINDLING 1,2О. В. Денисенко, 1Ол. Ол. Шандра, 1Р. С. Вастьянов 1,2О В Denisenko, 1Al Al Shandra, 1R S Vastyanov 1Одеський національний медичний університет, Одеса; 2Одеський національний університет ім. І. І. Мечникова, Одеса 1Odessa National Medical University, Odessa; 2 Odessa I. I. Mechnikov National University, Odessa Summary. The article deals with the characteristics of interictal neuronal activity changes in frontal cortex different layers of rats during the pentylenetetrazol kindling development. Two types of EEG activity were shown to be presented in these conditions. The 1st type of neuronal activity characterized by motor cortex II/III layers neuronal activity hyperactivation. The 2nd type neuronal activity characterized by the motor cortex deep (IV-VI) layers neurons hyperactivation. The authors conclude that the registered neuronal activity differences in the conditions of the chronic seizures experimental model mark the functional relationship between the epileptic and antiepileptic brain systems. They are also the basis for cortical networks formation and activation peculiarities further investigation in conditions of neurons excessive activation development during the prolonged convulsive influences. Key words: kindling, pentylenetetrazol, frontal cortex, interictal intracellular activity, proconvulsive and anticonvulsive mechanisms. ОСОБЕННОСТИ НЕЙРОНАЛЬНОЙ АКТИВНОСТИ ФРОНТАЛЬНОЙ КОРЫ КРЫС ПРИ ПЕНТИЛЕНЕТЕТРАЗОЛОВОМ КИНДЛИНГЕ. В работе исследовали особенности изменений интериктальной нейрональной активности в различных слоях фронтальной коры мозга крыс при формировании пентиленететразолового киндлинга. Показано, что в этих условиях у крыс формируются два типа ЭЭГ-активности. Первый тип нейрональной активности характеризуется гиперактивацией активности нейронов II/III слоев моторной коры. Второй тип нейрональной активности характеризуется гиперактивацией нейронов глубинных (IV-VI) слоев коры мозга. Авторы уверены, что зарегистрированные разновидности нейрональной активности в условиях развития экспериментальной модели хронической судорожной активности знаменуют функциональные взаимоотношения между активностью эпилептической и антиэпилептической систем мозга и являются основанием для дальнейшего выяснения особенностей формирования и активации кортикальных сетей при развитии чрезмерной активации нейронов при действии длительных просудорожных воздействий. Ключевые слова: киндлинг, пентиленететразол, фронтальная кора, интериктальная внутриклеточная активность, просудорожные и противосудорожные механизмы. Резюме. В роботі досліджували особливості змін інтеріктальної нейрональної активності у різних шарах фронтальної кори мозку щурів при формуванні пентиленететразолового кіндлінгу. Показано, що за цих умов у щурів відзначається формування двох типів ЕЕГ-активності. Перший тип нейрональної активності характеризується гіперактивацією активності нейронів II/III шару моторної кори. Другий тип нейрональної активності характеризується гіперактивацією нейронів глибинних (ІV-VI) шарів кори мозку. Автори впевнені, що зареєстровані різновиди нейрональної активності протягом розвитку експериментальної моделі хронічної судомної активності висвітлюють функціональні взаємовідносини між активністю епілептичної та антиепілептичної систем мозку та є підставою для подальшого з’ясування особливостей формування та активації кортикальних мереж при розвитку надмірної активації нейронів за умов дії тривалих просудомних впливів. Ключові слова: кіндлінг, пентиленететразол, фронтальна кора, інтеріктальна внутрішньоклітинна активність, просудомні та протисудомні механізми.